A new Cyrtodactylus (Squamata: Gekkonidae) from Phu Yen Province, southern Vietnam - Ziegler, Thomas; Phung, Trung My; Le, Minh Duc; Nguyen, Truong Quang (Zootaxa, 2013)
We describe a new species of the genus Cyrtodactylus based on five adult specimens from Dai Lanh Cape, Tuy Hoa District, Phu Yen Province, southern Vietnam. Cyrtodactylus kingsadai sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: maximum SVL of 94 mm; dorsal pattern consisting of a dark nuchal loop, continuous or partly interrupted neck band and four in part irregular transverse body bands between limbs; internasal single; dorsal tubercles in 17–23 irregular transverse rows; ventrals in 39–46 longitudinal rows at midbody; lateral skin folds present, without interspersed tubercles; precloacal pores 7–9 plus in total 3–7 femoral pores in males (1-4 femoral pores on each side) with precloacal and femoral pore series separated from each other by 7–9 poreless scales; enlarged femoral scales and precloacal scales present; postcloacal spurs three; subcaudal scales transversely enlarged. This is the 29th species of Cyrtodactylus known from Vietnam.